2021
DOI: 10.1001/jamapsychiatry.2021.1587
|View full text |Cite
|
Sign up to set email alerts
|

Charting New Phenomenological Paths for Empirical Research on Delusions

Abstract: Thirty years ago, John S. Strauss, MD, opened his article entitled "The Person with Delusions" with the T. S. Eliot quote, "And the end of our exploring Will be to arrive where we started And know the place for the first time [sic]." 1 Strauss describes the humbling experience of looking back at the work of phenomenologists, in-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…1 As this heritage is revived and critically revisited by contemporary phenomenologists, 2,3 moves are made towards cross-disciplinary and pluralistic approaches that can account for the inherent complexity of delusions beyond purely understanding them as erroneous beliefs. 4 In 2021, Feyaerts and colleagues 5 used intensive qualitative research methods, but literature directly investigating the lived experience and subjective apprehension of delusional phenomena in psychosis is still scarce and, to our knowledge, no systematic review on this literature has been done.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 As this heritage is revived and critically revisited by contemporary phenomenologists, 2,3 moves are made towards cross-disciplinary and pluralistic approaches that can account for the inherent complexity of delusions beyond purely understanding them as erroneous beliefs. 4 In 2021, Feyaerts and colleagues 5 used intensive qualitative research methods, but literature directly investigating the lived experience and subjective apprehension of delusional phenomena in psychosis is still scarce and, to our knowledge, no systematic review on this literature has been done.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, psychopathological research on delusion is quantitative 6 and deficit oriented, focusing on the search for a putative cognitive dysfunction invariably located in the person's mind or brain. 4 Within psychiatry, delusion research often relies on clinician-administered interviews or self-rating scales for assessing the severity of positive symptoms, and aims to detect causal factors involved in the development and persistence of delusions, such as reasoning biases (eg, jumping to conclusions), 7 low selfesteem and negative self-schemas, 8 and maladaptive appraisal processes driven by anxiety, worry, and depression. 9 Such work has led to significant advances, particularly in cognitive-behavioural treatment for patients with persecutory delusions and understanding of the role of affect and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this approach promotes a multi-layered understanding of the unique (i.e., idiographic) as well as shared (i.e., nomothetic) features of the experience of mental disorders. The integration of phenomenological insights could also open new research paths for clinical studies of delusions: here, it can help capture widely neglected areas of mental and experiential life beyond simple clinical severity, without lumping together forms of delusions that may only be loosely linked (Ritunnano et al ., 2021 ). When combined with standard clinical data, such as symptom severity or clinical stage, the integration of a phenomenologically informed framework allows us to increase the granular resolution of the psychopathological phenotype, thus contributing to improved, more accurate identification of caseness.…”
Section: Defining the Object Of Interest Or ‘Caseness’mentioning
confidence: 99%
“…Other studies have also shown that delusional content varies over time and are strongly associated with hallucinations and yet also occur independently or in association with other symptom clusters (81)(82)(83). Many researchers theorize that hallucinations and delusions exist along the same continuum and that the presence of hallucinations are directly related to the "meaning making" and the formation and maintenance of delusional reality (20,28,45,49,84). It is also pertinent to clinical practice and may even hold implications for mental health service provision: for example, those with the most severe hallucinations also tend to experience the most severe delusions, hence the potential need for extra clinical care and targeted interventions.…”
Section: Relationships Between Delusions Hallucinations Depression An...mentioning
confidence: 99%
“…Although FRS are more common in individuals with schizophrenia, they are no longer considered pathognomonic (12,24,25). Indeed, as influential as Jaspers' and Schneider's contributions are to the definition and categorization of delusions, there is unlikely to be a single criterion that lies at the core of the delusional experience and too much focus on narrow aspects of delusional thinking may even be counter-productive to the treatment and care of individuals with distressing delusions (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%